Presentation, pattern, and natural course of severe symptoms, and role of antibiotics and antibiotic resistance among patients presenting with suspected uncomplicated urinary tract infection in primary care: observational study. (5th February 2010) - Little, P; Merriman, R; Turner, S; Rumsby, K; Warner, G; Lowes, J A; Smith, H; Hawke, C; Leydon, G; Mullee, M; Moore, M V
Abstract : Objective To assess the natural course and the important predictors of severe symptoms in urinary tract infection and the effect of antibiotics and antibiotic resistance. Design Observational study. Setting Primary care. Participants 839 non-pregnant adult women aged 18-70 presenting with suspected urinary tract infection. Main outcome measure Duration and severity of symptoms. Results 684 women provided some information on symptoms; 511 had both laboratory results and complete symptom diaries. For women with infections sensitive to antibiotics, severe symptoms, rated as a moderately bad problem or worse, lasted 3.32 days on average. After adjustment for other predictors, moderately bad symptoms lasted 56% longer (incidence rate ratio 1.56, 95% confidence interval 1.22 to 1.99, P<0.001) in women with resistant infections; 62% longer (1.62, 1.13 to 2.31, P=0.008) when no antibiotics prescribed; and 33% longer (1.33, 1.14 to 1.56, P<0.001) in women with urethral syndrome. The duration of symptoms was shorter if the doctor was perceived to be positive about diagnosis and prognosis (continuous 7 point scale: 0.91, 0.84 to 0.99; P=0.021) and longer when the woman had frequent somatic symptoms (1.03, 1.01 to 1.05, P=0.002; for each symptom), a history of cystitis, urinary frequency, and more severe symptoms at baseline. Conclusion Antibiotic resistance and not prescribing antibiotics are associated with a greater than 50% increase in the duration of more severe symptoms in women with uncomplicated urinary tract infection. Women with a history of cystitis, frequent somatic symptoms (high somatisation), and severe symptoms at baseline can be given realistic advice that they are likely to have severe symptoms lasting longer than three days.